Pengaruh Partisipasi Anggaran dan Akuntabilitas Publik Terhadap Kinerja Aparatur - Nur Wahdha Hijriyah Haiqal; Mappamiring (Insan Cita Bongaya Research Journal, 2024)
This study aims to test and analyze the effect of budget participation and public accountability on the performance of the apparatus in the Gowa District Financial and Asset Management Agency. Data collection used primary data obtained from filling out questionnaires using saturated sample techniques (census). The population in this study was the entire State Civil Apparatus (ASN) working at the Gowa Regency Regional Financial and Asset Management Agency which amounted to 34 people, while the sample taken by the number of observations was 34 people. The data obtained were analyzed using multiple linear regression analysis. The results showed that budget participation has a positive and significant effect on the performance of the apparatus, public accountability has a positive and significant effect on the performance of the apparatus